2009
DOI: 10.1016/j.pain.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B62 and HLA-DQ8 are associated with Complex Regional Pain Syndrome with fixed dystonia

Abstract: Complex Regional Pain Syndrome (CRPS) is clinically characterized by pain in combination with sensory, autonomic, and motor symptoms that may include weakness, tremor, myoclonus and dystonia of the affected limb(s). The syndrome is multifactorial in origin and mostly attributed to tissue injury. There is some evidence that the human leukocyte antigen (HLA) system plays a role in the pathophysiology of CRPS, but previous studies lacked power. Here we performed the most extensive study investigating the contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 35 publications
1
56
0
8
Order By: Relevance
“…Evidence for genetic factors, especially the involvement of the HLA complex on chromosome 6, in CRPS is increasing [12,27,33,46,48]. Despite these achievements, no single genetic factor has been identified in CRPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for genetic factors, especially the involvement of the HLA complex on chromosome 6, in CRPS is increasing [12,27,33,46,48]. Despite these achievements, no single genetic factor has been identified in CRPS.…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome may cluster in families [1,6,11,16,19,23,49]. Although several genetic associations between CRPS and the HLA gene complex on the short arm of chromosome 6 (6p21.3) have been reported [12,27,33,46,48], to date no single causative gene has been identified. In contrast to CRPS, there have been many successes in identifying genes for primary dystonia (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology is not known in detail, and factors such as limb immobilization, 1 ischemia with reperfusion, 2 small-fiber neuropathy, 3 neurogenic inflammation, 4 sympathetic denervation followed by supersensitivity, 5 and genetic mechanisms 6 have all been suggested to play a pathophysiologic role. CRPS is often divided into two subtypes: an acute warm and vasodilated state and a chronic cold state with vasoconstriction.…”
mentioning
confidence: 99%
“…Relatives of patients with CRPS CRPS are more often spontaneous and at younger ages [18]; SDRC is no association between mitochondrial disorders in Young It found that some genes of major histocompatibility complex (HLA) are found more in CRPS and other less frequently; HLA-B62 and HLA-DQ8 alleles were significantly associated with CRPS [19] and TNF2 allele is most commonly found in CRPS hot phase.…”
Section: Genetic Factorsmentioning
confidence: 99%